Estudo teórico - experimental de um sistema de refrigeração por absorção de duplo efeito em série usando o par água / brometo de lítio. - Rocha, Márcio Andrade (2010)
The present paper describes an theoretical-experimental study of an double effect absorption refrigeration machine in series that uses the waste heat from the exhaust fumes of an internal combustion engine as an energy source for the steam generator. Stress that the machine being used was designed and built on the premises of the Federal University of Paraíba in the Institute of Sustainable Energy and recog-IES laboratory, Cooperative Research Network North / Northeast Natural Gas. This study aims to describe the constructive aspects of a pilot plant with cooling capacity of around 0.5 TR, emphasizing discussion relation to the accuracy, errors, difficulties, problems identified and solutions found during the construction processes, testing, operation, data acquisition and evaluation of the pilot plant.